2013
DOI: 10.1177/0018726712465657
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to retirement: A career stage analysis of retirement age expectations

Abstract: In western economies with aging populations, organizations are increasingly challenged to understand and manage employees' retirement expectations. At the same time, employees' relationships to retirement decisions and the age at which they expect to retire are likely to change as their careers unfold. This article seeks to inform the careers and management literatures on factors contributing to retirement intentions at different career stages. Using a sample of mid-and late career professionals with MBAs, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 78 publications
(100 reference statements)
4
49
0
4
Order By: Relevance
“…First, we found that job satisfaction does not exert a direct effect on intended retirement age at any level of household income category and so Hypothesis 1 was not supported with our data. This finding is consistent with the insignificant results found in a number of other studies (McCune and Schmitt, 1981; Taylor and Shore, 1995; Adams and Beehr, 1998; Adams, 1999; Beehr et al, 2000; Davies and Cartwright, 2011; Smith et al, 2011; Post et al, 2013). It seems that we may cautiously conclude that a higher household income does not relax the individual’s complex decision-making process around intended retirement age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, we found that job satisfaction does not exert a direct effect on intended retirement age at any level of household income category and so Hypothesis 1 was not supported with our data. This finding is consistent with the insignificant results found in a number of other studies (McCune and Schmitt, 1981; Taylor and Shore, 1995; Adams and Beehr, 1998; Adams, 1999; Beehr et al, 2000; Davies and Cartwright, 2011; Smith et al, 2011; Post et al, 2013). It seems that we may cautiously conclude that a higher household income does not relax the individual’s complex decision-making process around intended retirement age.…”
Section: Discussionsupporting
confidence: 93%
“…The findings in this study are also consistent with those of Post et al (2013), who reinforced the importance of financial concerns in influencing retirement intentions, and highlight the importance of context in understanding of socio-economic status in the dynamics of the relationship between work and retirement (Hennekam and Herrbach, 2013). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A centralidade do trabalho aparece como significativa somente para a percepção financeira, demonstrando que o afastamento da vida profissional pode proporcionar melhor vislumbre de futuro financeiro (Selig & Valore, 2010;Topa, Moriano, & Moreno, 2012). Ainda que se discuta que a aposentadoria não necessariamente implica o abandono do trabalho, os dados indicam que promover essa quebra das atividades profissionais como centrais na vida pode facilitar o desenvolvimento de um ponto de vista mais positivo quanto ao futuro sem o trabalho (Post, Schneer, Reitman, & Ogilvie, 2013).…”
Section: Discussionunclassified
“…(See McCullough and Laurenceau [] for a longitudinal review of self‐rated health.) Single‐item measures of self‐rated health have been used extensively in national probability samples in the United States and Europe and in longitudinal research on managers (Post, Schneer, Reitman, & olgilvie, ).…”
Section: Methodsmentioning
confidence: 99%